THE EFFECT OF ENTREPRENEURIAL ORIENTATION ON SOCIAL MEDIA MARKETING ADOPTION AND MSME PERFORMANCE: THE MODERATING ROLE OF INNOVATION ABILITY - Muhammad Al Hafis; Naufal Bachri; Mohd. Heikal; Ikramuddin; Adnan; Heriyana (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to examine the influence of entrepreneurial orientation on the adoption of social media marketing and the performance of MSMEs: the moderating role of innovation capability. This study was conducted on 120 MSMEs in North Aceh Regency, and data collection was carried out through questionnaires distributed through Google Forms. The data analysis tool used Structural Equation Modeling (SEM) operated with Amos. The results of the study found that entrepreneurial orientation significantly influenced the adoption of social media marketing and the performance of MSMEs. The adoption of social media marketing and innovation capability also significantly improved the performance of MSMEs. And in testing the mediation effect of social media marketing adoption significantly mediated the influence of customer value on customer loyalty. Furthermore, in testing the moderation effect, innovation capability significantly moderated the influence of social media marketing adoption on MSME performance. The results of this study are expected to provide important contributions for stakeholders in formulating MSME business marketing policies and strategies in the future